Pre- and postnatal maternal depressive symptoms associate with the local connectivity of the left amygdala in 5-year-olds - Vartiainen, Elena (My University, 2023)
Maternal pre- and postnatal depressive symptoms influence brain development in offspring. This effect mediates child brain development through intrauterine conditions as well as ways of parenting and mother-child interaction. This thesis investigated whether maternal pre- and postnatal depressive symptoms associate with child’s whole brain regional homogeneity and seed- based connectivity of the bilateral amygdala at 5-years-of-age based on the sample available from FinnBrain Birth Cohort Study (N=68). Maternal depressive symptoms were assessed at gestational week 24, and 3 months, 6 months, and 12 months postnatal. Children’s brain imaging data were acquired with task-free functional magnetic resonance imaging (fMRI) at the age of 5 years in 7 min scans while watching the Inscapes movie. Regional homogeneity (ReHo) and seed-based connectivity maps of the bilateral amygdalae were created from the fMRI data. We found that maternal depressive symptoms were positively associated with ReHo values of the left amygdala. The association was strongest with the maternal depressive symptoms at three months postnatal. Seed-based connectivity analysis did not reveal associations with distal connectivity of the left amygdala region and maternal depressive symptoms. These results suggest that maternal depressive symptoms during pregnancy and especially soon after birth may influence offspring’s neurodevelopment related to emotional processing in fundamental ways.
Keywords: fMRI, maternal depression, child brain development, amygdala, ReHo